ANALISIS HUBUNGAN INFLASI, PMA, PENYERAPAN TENAGA KERJA DAN PERTUMBUHAN EKONOMI INDONESIA - Nurvira Nurvira; Ichsan Ichsan (LPPM UNIMAL, 2021)
This study examined the relationship between inflation, foreign investment (FDI), and employment with economic growth. This study used secondary data from 1990 to 2020. The data were analyzed using the vector autoregression (VAR) analysis method. The results showed that inflation had no significant effect on economic growth. Vice versa, economic growth had no significant effect on inflation. FDI had a negative and significant effect on economic growth. Furthermore, economic growth had no significant effect on FDI. The absorption of labor did not have a significant effect on economic growth. Vice versa, economic growth had no significant effect on employment. The government should strengthen the applicable regulations, especially regulations regarding FDI to make a more positive contribution to economic growth.